A Dél-Dunántúl területfejlesztési koncepciójának alapelemei - Faragó, László; Horváth, Gyula (Tér és Társadalom, 1995)
South Transdanubia is less developed and copes with more problems than the Middle and Northern part of Transdanubia. However, the crisis is not as extreme as in North East Hungary, and there is more hope for a better outcome than in regions in deeper crisis. Therefore, we need a comprehensive programme for the region. At the same time it is obvious that significant results cannot be achieved without co-operation based resolution and without the existence of suitable institutions and resources. lt was a promising sign in the planning and implementation of the programme that the various actors of the region did not expect development to be fostered by the sate only, but they themselves were eager to contribute. At the very beginning, many of these actors were drawn into the preparations of the programme. Also, the process of planning the concept proved quite significant in regard of regional integration a necessary element for development. Often, the process of planning also served as the framework within which interests were asserted. A further sign anticipating the success of the programme was that several organisations of several types and levels contributed to the implementation with information, co-operation and also with financial resources. Parallel to the completion of the concept, and because of the lack of a regional middle level, the South Transdanubian Foundation for Regional Development was established by the counties of Baranya, Somogy, Tolna and Zala. In the advisory board of this institution there are representatives of the government, but there are also representatives of the local governments, politicians, universities and the scientific and economic organisations of the region. These public funds may be the forerunner of the regional development board that has been recommended in the draft of the regional development bill now under negotiation. On the basis of these promising signs, the government decided that South Transdanubia would be the next major region for which it would prepare a development concept. The regional development concept was included in the 1994 government programme. The new government did not reinforce this task as specifically labelled one. The Ministry of the Environment and Regional Development, which is responsible for this task, based upon preliminary inquiries and from its poor resources for planning, ordered from the Hungarian Academy of Sciences, Centre for Regional Studies the preparation of an economy and competition based development concept. The paper summarises basic elements of the regional development concept, including priorities, programmes and institutional organisation of implementation.